Phytochemicals from Corchorus olitorius methanolic extract induce apoptotic cell death via activation of caspase-3, anti-Bcl-2 activity, and DNA degradation in breast and lung cancer cell lines - Ali Mohamed Alshabi; Saad Ahmed Alkahtani; Ibrahim Ahmed Shaikh; Mohamed A.A. Orabi; Basel A. Abdel-Wahab; Ismail A. Walbi; Mohammed S. Habeeb; Masood Medleri Khateeb; Joy H. Hoskeri; Arun K. Shettar; Syed Mohammed Basheeruddin Asdaq (Journal of King Saud University: Science, 2022)
Objectives: The main objective of the present research is to provide GC–MS and LC-MS phytochemcial profiling of Corchorus olitorius along with Flow cytometry based mechanistic investigation of cytotoxic activity of its extracts against breast and lung cancer cell lines. Methods: The Soxhlet extraction method was used in the sequential extraction of C. olitorius. The phytochemical profiling was done using LC-MS and GC–MS techniques, and total phenolic and flavonoid content was determined. The cytotoxicity was studied against non-cancerous L929 cells and cancerous MCF-7 and A549 cell lines using MTT assay, followed by flow cytometry based molecular mechanisms study through anti-Bcl-2 assay, Caspase-3, and DNA fragmentation (TUNEL assay). Results: The C. olitorius methanolic extract showed the phenolic compounds and flavonoids as a major constituents with 699 µg GAE/g of dw and 1361.50 µg QE/g of dw, respectively. The GC–MS and LC-MS results confirmed the presence of active phytochemicals. Toxicity study against L929 cell line revealed that methanol extract proved to be less toxic with a higher IC50 value i.e. 227.84 µg/ml. Cell viability MTT assay for methanol extract against MCF-7 and A549 cell lines revealed significant results with IC50 values of 20 µg/ml and 12.45 µg/ml, respectively. The flow cytometry based molecular marker studies showed that the extract successively induced early and late apoptosis in tested breast and lung cancer cells through activation of Caspase-3 with inhibition of Bcl-2 protein and induced cell death through DNA damage. Conclusion: Collectively, these findings show that the methanol extract of C. olitorius inhibits breast cancer and lung cancer cell lines with significant cytotoxic activity. Thus, C. olitorius would be a promising source of chemopreventive agents that warrant further investigation to find lead compounds with cancer chemotherapeutic potential.